2021
DOI: 10.26714/jsm.4.1.2021.146-153
|View full text |Cite
|
Sign up to set email alerts
|

Triwaca dan Literacycloud: Ragam Membaca Menyenangkan selama Pandemi Virus Corona

Abstract: The outbreak of Corona virus pandemic is changing the face of the education process in various parts of the world. Lots of the educational processes are transformed into online or learning from home. In spite of this, it was found that some teachers experienced difficulties administering online teaching. This phenomenon moves the community service team to organize a varied, interactive, and fun learning process for educators at the elementary school level in Deli Serdang Regency, North Sumatra. A total of 90 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[5] This attendance system can manage attendance data to be more organized to increase time efficiency in preparing reports. [6] The fingerprint attendance system can improve the paperless system, thereby reducing operational costs in the work process at the 'MurniSadar' English Course Pematangsiantar, especially in student attendance.…”
Section: Discussionmentioning
confidence: 99%
“…[5] This attendance system can manage attendance data to be more organized to increase time efficiency in preparing reports. [6] The fingerprint attendance system can improve the paperless system, thereby reducing operational costs in the work process at the 'MurniSadar' English Course Pematangsiantar, especially in student attendance.…”
Section: Discussionmentioning
confidence: 99%
“…According to study findings for human resource planning based on observations and interviews with resource persons conducted by researchers, there are the following research findings: (1) SMA Negeri 8 Medan's HR planning is conducted by analysis of causes generating changes in the workforce, through a once-a-year evaluation that is conducted periodically; (2) create a strategy to ascertain the demand for any staff and the requirements of potential candidates who will be hired later; (3) prior to performing and deciding on the implementation of the recruitment program, analyze internal sources; (4) Implementation of the HR planning program associated with the school administration's policy to hire honorary personnel.…”
Section: Human Resource Planning At Sma Negeri 8 Medanmentioning
confidence: 99%
“…Information and communication technology undoubtedly affect many facets of life as the borders between humans, machines, and other resources converge. One of them is the effect on Indonesia's educational system [1], [2], [3]. With a system that is strongly connected to both the actual world and the virtual world, Society 5.0 promises a humancentered society that strikes a balance between the advancement of economic technology and addressing social issues.…”
Section: Introductionmentioning
confidence: 99%
“…They also can refresh it back at home as their references. A few studies have found that learners who used the study-from-home learning plan made little progress throughout the epidemic timeframe (Kisno et al, 2021;Muhlisin et al, 2022;Per et al, 2021).…”
Section: Suggestions In Continuing the Process Of Teaching And Learni...mentioning
confidence: 99%